Exploring bismuth-substituted yttrium iron garnet: Insights into structural, optical, and dielectric characteristics - Hazam R.; Maity M.; Verma S.; Singh R.; Bhoi B. (My University, 2025)
Magnetic garnets, a diverse group of magnetic insulating materials, have been the subject of extensive research for decades, owing to their versatility and potential for a wide range of applications. In this study, we synthesized Bismuth-Substituted Yttrium Iron Garnet (BiY2Fe5O12: BiYIG) using the solid-state reaction method to explore its structural, optical, and dielectric characteristics. X-ray diffraction analysis revealed the attainment of a pure cubic garnet phase in BiYIG, with a lattice parameter of 12.444 Å. Using UV–visible spectroscopy, we determined that the optical band gap of BiYIG is 2.2 eV, indicating n-type semiconductor behavior. We conducted a thorough investigation of the dielectric properties, examining capacitance, dielectric constant, dielectric loss, conductivity, impedance, and modulus, as functions of frequency and temperature. The impedance results revealed that the dielectric relaxation at room temperature was dominated by a Debye-type process, with a shift to a non-Debye-type process becoming apparent as temperature increased. Comprehensive analysis sheds light on the material's transport phenomena and optical attributes, offering insights into the potential of BiYIG for applications in magneto-dielectric and magneto-optical domains, given its high dielectric constant with low dielectric loss, and promising optical properties. These findings position BiYIG as a versatile material and underscore its suitability for advanced applications in future technological developments. © 2024 The Author(s)